1026 Assessing the Reliability of 3D Imaging for Wound Measurements. (12th October 2021) - Hitchman, L; Cai, P; Sethi, S; Stirrup, A; Lathan, R; Sidapra, M; Smith, G; Carradice, D; Chetter, I
Abstract: Aim: To investigate the inter and intra reliability of using 3D imaging to measure wounds. Method: 20 wound models of 4 different shaped wounds in 5 different colours were created from plastic mouldable beads. 3D images were taken using the BlasterX Senz3D camera and measured using the GPC Wound Measure application (version 3.15.0.0, UK). Intra-user reliability was determined comparing 20 wound measurements of each wound model. Inter-user reliability was determined by 5 different clinicians photographing each model and independently measuring each wound photo. The inter- and intra-rater measurements for wound surface area and volume were compared using the ICC and differences from the overall mean plotted on Bland-Altman graphs. Results: The interclass co-efficient (ICC) for inter-rater reliability in measuring surface area was 0.958 (95% CI 0.919-0.981, p < 0.005). The intra-rater reliability when measuring wound surface area was 0.996 (95% CI 0.993-0.998, p < 0.005). For wound volume, the ICC for inter-rater reliability was 0.925 (95% CI 0.857-0.967, p < 0.005) and 0.999 (95% CI 0.998-0.999, p < 0.005) for intra-user reliability. 5.5% of measurements were outside 2 SD of the mean for wound volume. Conclusions: 3D imaging offers a quick, reliable, and easy to use solution to measuring wounds. We have shown it is a reliable and reproducible method of measuring wounds between different clinicians.